2003
DOI: 10.1071/ea02175
|View full text |Cite
|
Sign up to set email alerts
|

The potential of Brassica green manure crops for controlling root-knot nematode (Meloidogyne javanica) on horticultural crops in a subtropical environment

Abstract: In glasshouse experiments, Meloidogyne javanica reproduced on Brassica juncea, B. napus and BQMulch, a commercial biofumigant crop consisting of both B. napus and B. campestris. Although nematode multiplication rates were only 3–23% of the rate on a highly susceptible crop (tomato), they were high enough to suggest that Brassica rotation crops will increase root-knot nematode populations to potentially damaging levels in situations where temperatures do not limit nematode reproduction. A field study showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 0 publications
0
37
0
1
Order By: Relevance
“…The vines in the pots that received the green manure also experienced a growth response, indicating the secondary effect of the green manure applications. Stirling and Stirling (2003) sowed brassicas in field soil and incorporated the green material into the soil at a depth of 180 mm after 10 weeks. A root gall index indicated a significant reduction in the M. javanica root galls where brassicas were incorporated at an earlier stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vines in the pots that received the green manure also experienced a growth response, indicating the secondary effect of the green manure applications. Stirling and Stirling (2003) sowed brassicas in field soil and incorporated the green material into the soil at a depth of 180 mm after 10 weeks. A root gall index indicated a significant reduction in the M. javanica root galls where brassicas were incorporated at an earlier stage.…”
Section: Discussionmentioning
confidence: 99%
“…The reproduction of M. javanica on certain brassica crops was compared to that on other crops that were not known to have biofumigation properties (Stirling & Stirling, 2003). The crops that were included in these trials were B. juncea cv.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of DMP is also stressed in work done by Rahman and Somers (2005), who found that the suppression of M. javanica in vineyards was better with higher biomass being applied to the infested soil. Stirling and Potter (1998) also found that at least 2 t/ha of Brassica biomass are needed for a significant biocidal impact, while Stirling and Stirling (2003) indicated a reduction of M. javanica after the application of 17 ton DMP/ha in comparison to the impact of lower DMP, but could not determine whether the reduction was specifically due to the ITC release or perhaps due to other, secondary aspects. The DMP of Nemat (MC) was below 2 tons/ha for all three seasons and, bearing in mind the work by Stirling and Potter (1998), this treatment is not expected to have a dramatic impact on the M. javanica numbers, as the amount of biomass produced and therefore the potential to form ITC was very low.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, radishes in this study may have a more biofumigation potential than other brassica plants if utilized as a green manure amendment. In order to increase the success of biofumigation, non-host or poor host species for target nematode species or population should be grown especially when soil temperature is suitable for nematode activity (Stirling and Stirling 2003;Pattison et al, 2006;Avato et al, 2013). Otherwise, nematode population increases in the soil during cultivation before the incorporation of biofumigant plants into the soil.…”
Section: Discussion:-mentioning
confidence: 99%